VIEWS ON THE ORGANISATION AND CONDUCT OF INDIVIDUAL TRAINING OF OFFICERS OF MILITARY COMMAND AND CONTROL BODIES - Repilo, І.Е.; Kamalov, Е.V.; Klyuchak, О.М; Репіло, Ю.Є.; Георгадзе, О.А.; Винокуров, Д.В.; Камалов, Є.В.; Ключак, О.М.; Чайковська, О.Є. (Військовий інститут Київського національного університету імені Тараса Шевченка, 2024)
Trends in the development of modern military conflicts, in particular the large-scale armed aggression of the Russian Federation against our country, improvement of forms and methods of employment of troops (forces), development of firearms, increase in the scope of tasks involving military command and control, implementation of principles, procedures and standards adopted by the armed forces of NATO member states, require a set of measures aimed at improving operational training. One of the components of operational training is the individual training of servicemen of the military command and control, which is conducted with the aim of developing their individual capabilities to perform tasks effectively independently and as part of the military command and control. Directly planning the use, commanding groups of troops (forces) in operations (combat actions), organising interaction and comprehensive support is carried out by the officers of the military command and control. The quality of performance of their tasks depends on the level of their training, which is the result of their individual training. Thus, there is a need to improve the individual training of officers.Based on the scientific and methodological approaches to assessing the effectiveness of individual training of servicemen and the experience of its conduct in the military education institutions of the Armed Forces of Ukraine during 2022-2024, the article presents the authors' views on the organisation and conduct of individual training of officers in military administration. The implementation of the proposed views involves: development of standards of functional responsibilities for a typical position, introduction of individual tasks, creation of web resources, introduction of modern forms and methods of training.The results of the study can be used in the development of guidelines regulating the organisation and conduct of individual training of officers in the military command and control, as well as in the course of further research in this area in academic institutions.

ійської федерації проти нашої держави, удосконалення форм та способів застосування військ (сил), розвиток засобів вогневого ураження, збільшення обсягу завдань до виконання яких залучаються органи військового управління (ОВУ), впровадження принципів, процедур і стандартів, прийнятих у збройних силах держав-членів НАТО, вимагають проведення комплексу заходів, спрямованих на вдосконалення оперативної підготовки. Однією із складових оперативної підготовки є індивідуальна підготовка військовослужбовців ОВУ, яка проводиться з метою розвитку їх індивідуальних спроможностей для ефективного виконання завдань самостійно та у складі ОВУ. Безпосередньо планування застосування, управління угрупованнями військ (сил) в операціях (бойових діях), організацію взаємодії та всебічного забезпечення здійснює офіцерський склад ОВУ. Якість виконання покладених на них завдань залежить від рівня їх навченості, який являється результатом їх індивідуальної підготовки. Отже, виникає потреба в удосконаленні індивідуальної підготовки офіцерського складу.На основі науково-методичних підходів з оцінювання ефективності індивідуальної підготовки військовослужбовців та досвіду її проведення в ОВУ Збройних Сил (ЗС) України протягом 2022 - 2024 років у статті авторами викладено погляди щодо організації та проведення індивідуальної підготовки офіцерського складу в органах військового управління. Реалізація запропонованих поглядів передбачає: розробку стандартів функціональних обов’язків для типової посади, запровадження індивідуальних завдань, створення вебресурсів, впровадження сучасних форм і методів навчання.Результати проведеного дослідження можуть бути застосовані при розробці керівних документів, що регламентують питання організації та проведення індивідуальної підготовки офіцерського складу в ОВУ, а також у ході подальших досліджень з даного напряму у наукових установах.
ПОГЛЯДИ ЩОДО ОРГАНІЗАЦІЇ ТА ПРОВЕДЕННЯ ІНДИВІДУАЛЬНОЇ ПІДГОТОВКИ ОФІЦЕРСЬКОГО СКЛАДУ ОРГАНІВ ВІЙСЬКОВОГО УПРАВЛІННЯ
Keywords: індивідуальна підготовка; органи військового управління; організація підготовки; омпетентності; ресурси; форми і методи навчання; individual training; military command and control; organisation of training; competences; resources; forms and methods of training